IMPACT OF ANTENATAL CARE ON MATERNAL MORBIDITY IN THREE MILITARY HOSPITALS OF PUNJAB, PAKISTAN: Antenatal Care in Maternal Morbidity - Akbar, Rizwana; Azam, Naila; Mughal, Fatima Ali Raza; Tariq, Ahmed; Wajahat, Maira (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the impact of antenatal care on maternal morbidity.Study Design: Comparative cross-sectional study.Place and Duration of Study: Obstetric Departments of three military hospitals in Northern Punjab cities of Rawalpindi, Jehlum and Mangla, from Jan to Mar 2019.Methodology: Data of all mothers who gave live births in the selected military hospitals were collected. These mothers were classified as booked and unbooked on the basis of number of antenatal care visits. Maternal morbidities and complications of pregnancy were recorded. The data were analyzed using Statistical Packages for Social Science (SPSS) version 20.Results: In our study, 254 (8.8%) of mothers were unbooked, 2273 (78.8%) were partially booked and 358 (12.4%) were booked. 894 (31%) mothers did not have any co-morbidity while 1991 (69%) mother had co-morbidity. Out of 749 (27.5%) mothers had anaemia, 869 (30.1%) had hypertension, 141 (30.1%) had diabetes mellitus, 24 (0.8%) cardiac disease, 39 (1.4%) had tuberculosis, 9 (0.3%) had liver disease 13 (0.5%) had kidney disease, 69 (2.4%) had allergies while 33 (1.1%) had other diseases. These complications were significantly greater in unbooked patients as compared to booked patients (p